2007
DOI: 10.2174/1874256400701010024
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effects of Dietary Habits on Menstrual Disorders in Young Women

Abstract: It has been accepted that food customs are closely associated with quality of life in women of the reproductive age. Food customs are speculated to not only influence the present life style but also to induce gynecological disorders such as dysmenorrhea and irregular menstruation. Although there is no constant definition of regular or normal menstruation, epidemiologic evaluation of menstrual cycle has been becoming an important issue. In addition, latent development of organic diseases such as endometriosis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 106 publications
(100 reference statements)
0
5
1
Order By: Relevance
“…This finding is considered normal as adolescents in this present study were experiencing menarche at the age 13-14 years old, and most of our respondents were 16-17 years old when the study was conducted. The previous study by Fujiwa, et al, suggested that about 25-40% of girls were experiencing irregular menstruation or did not ovulate until four years after menarche because positive estrogen feedback system on hypothalamus and pituitary is still developing [9]. However, we found that the second common disturbance reported by the girls in this present study was abnormal blood volume (50%) and around 50% girls reported to have at least two types of menstrual disorder.…”
Section: Discussioncontrasting
confidence: 51%
“…This finding is considered normal as adolescents in this present study were experiencing menarche at the age 13-14 years old, and most of our respondents were 16-17 years old when the study was conducted. The previous study by Fujiwa, et al, suggested that about 25-40% of girls were experiencing irregular menstruation or did not ovulate until four years after menarche because positive estrogen feedback system on hypothalamus and pituitary is still developing [9]. However, we found that the second common disturbance reported by the girls in this present study was abnormal blood volume (50%) and around 50% girls reported to have at least two types of menstrual disorder.…”
Section: Discussioncontrasting
confidence: 51%
“…These have negative effects on ovarian functions [ 25 ]. The type of fatty acids concerned with menstrual disorders, for example, omega-3 fatty acids (e.g., fish and canola oil), reduced dysmenorrhea because of anti-inflammatory effects [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…(4) Dysmenorrhea was assessed by asking them with or without severe pain during menstruation. (5) PMS was defined as one or more of the following symptoms starting 10 days before menstruation and disappearing at the start of period: rapid mood changes, depression, painful or tender breasts and bloating or swelling of the abdomen [ 15 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Progesterone is crucial for preparing the uterine lining for implantation and maintaining a healthy pregnancy if fertilization occurs. Imbalances in progesterone levels can lead to irregularities in the menstrual cycle and contribute to premenstrual symptoms [25]. Junk foods are often deficient in essential micronutrients like vitamin B6, calcium, magnesium, and potassium.…”
Section: Intake Of Junk Foodmentioning
confidence: 99%